Studies on conidial germination and factors affecting disease development of Stemphylium blight of onion - and L.S. SURAG, S.S. JAKHAR, J.C. DURAN (Indian Phytopathology, 2002)
A conidial suspension of S. vesicarium prepared from a 10 d-old culture had a lag period of at least 2 h for germination on the leaf surface of onion (Allium cepa) cv. Hisar-2. After 32 hours, 76% of the conidia had germinated. In different solutions, the max. av. conidial germination (63.30%) was recorded in dew drops followed by glucose solution (55.50%), tap water (46.60%) and distilled water (33.10%). There was a steep increase in conidial germination in all solutions, and on plant foliage, after 8 h of incubation and thereafter, it gradually increased up to 32 h of incubation. Disease intensity increased with increase in inoculum concn (5000 conidia/ml) but declined when inoculum concn was further increased (10 000 conidia/ml). However, this decline was not statistically significant. Max. disease intensity was recorded when 90-120 d-old plants were inoculated with 21 d-old cultures. The infectivity of cultures increased up to 21 days but declined after 30 days. Plants of all ages (10-120 d) were almost equally susceptible. The fungus required at least 16 h in a saturated atmosphere for initiation of disease.